PERAN KBIH MERESTORASI MENTAL JAMAAH HAJI MANDIRI: STUDI DI KOTA TANGERANG BANTEN - Muhammad Ishom (Harmoni, 2017)
The role of the Hajj Guidance Group (KBIH) has not been effective as the implementation of the independent Hajj mentalty’s program, such as self-sustaining travel, Manasik-al-hajj, and health. That’s factor are; (1) there is trade orientation of trade orientation, (2) distinction between independent pilgrimage and group hajj (3) pilgrimage following the culture of patriarchi (3) prestice group.